Time of ball possession and visual search in the decision-making on shooting in the sport of futsal - Corrêa, U. C.; Oliveira, T. A. C. D.; Clavijo, F. A. R.; Leticia da Silva, S.; Zalla, S. (International Journal of Performance Analysis in Sport, 2020)
This study investigated how futsal players deal visually with information in interpersonal coordination scenarios when making decisions on shooting. The sample consisted of thirty-two sequences of play, ranging from 0.36 to 5.28 seconds in length, in which 32 experienced players - men (M = 19.36, SD = 1.32) - performed a shot wearing Tobii Glasses 2 eye-tracking, across 18 futsal games. Relative angles formed by the interaction of a shooter to the defender closest to him/her and the goalkeeper were used to capture interpersonal coordination for shooting. Variability in visual search was calculated on the basis of the number of times "quiet eyes" changed over the course of the sequence of play. The results showed that variabilities in the third (2.80) and fourth (5.37) quartiles of ball possession time were higher than those of the first (1.55) and second (1.70) quartiles. They also revealed that variabilities in visual search did not differ in relation to the magnitude, velocity and variability of the relative angles. It was concluded that the longer the ball possession time, the greater the variability in visual search. It would appear that through visual search, players look for the same - optimal - angular interpersonal relationship.